2018
DOI: 10.1016/j.mambio.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing reservoir water levels improve habitat quality for Asian elephants

Abstract: The following work is licensed under a Creative Commons: Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0) License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This disparity may be partly explained by the lower mean AOO of elephants for the other Asian elephant range states (14.4 ± SD 13% of country area; Leimgruber et al, 2003). Compared to most range states, the greater extent of elephant range outside protected areas in Sri Lanka may be another contributory factor, as disturbed habitats support higher elephant densities (Fernando & Leimgruber, 2011; Pastorini et al, 2013; Evans et al, 2018; Ranjeewa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity may be partly explained by the lower mean AOO of elephants for the other Asian elephant range states (14.4 ± SD 13% of country area; Leimgruber et al, 2003). Compared to most range states, the greater extent of elephant range outside protected areas in Sri Lanka may be another contributory factor, as disturbed habitats support higher elephant densities (Fernando & Leimgruber, 2011; Pastorini et al, 2013; Evans et al, 2018; Ranjeewa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Habitats with an intermediate disturbance regime support higher densities of Asian elephants than undisturbed forests (Fernando & Leimgruber, 2011; Pastorini et al, 2013; Ranjeewa et al, 2018; Evans et al, 2018). In an analysis of Borneo elephant Elephas maximus borneensis ranging and habitat use, degraded and secondary forests were found to be of higher suitability for elephants than primary forests, but their value for elephant conservation is largely unappreciated (Evans et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sources in Table 4 Gestation length Minimum (624 days) Mean (641 days) Maximum (667 days) Short-day breeding (total/beyond 11.75°S) 8 (21)/2 (8) 9 (21)/2 (8) 7 (21)/1 (8) Long-day breeding (total/beyond 11.75°S) 13 (21)/6 (8) 12 (21)/6 (8) 14 (21)/7 (8) Change S-L/L-S 2/1 -2/0 the same pattern for semi-captive Asian elephants in timber camps in Myanmar: the highest overall body weight was measured during monsoon months and the lowest towards the end of the dry season. By contrast, a recent study on Sri Lankan elephants found that their body condition was better in the dry season, probably because the receding water levels in reservoirs offered space for fresh grass regrowth (Ranjeewa et al 2018). As described above, freeranging Asian elephants at higher latitudes and semi-captive Asian elephants showed a moderate preference for long-day breeding, even though the long-day period more often coincided with the dry season when body condition was lower.…”
Section: Nutrition and Body Conditionmentioning
confidence: 88%
“…By contrast, a recent study on Sri Lankan elephants found that their body condition was better in the dry season, probably because the receding water levels in reservoirs offered space for fresh grass regrowth (Ranjeewa et al. ). As described above, free‐ranging Asian elephants at higher latitudes and semi‐captive Asian elephants showed a moderate preference for long‐day breeding, even though the long‐day period more often coincided with the dry season when body condition was lower.…”
Section: Factors Influencing Reproduction In Free‐ranging Semi‐captimentioning
confidence: 90%
“…However, in practice, the majority of vehicles to the park take selected and preferred routes, leading to an uneven distribution of vehicles within the park itself. Safaris in the UWNP are limited to approximately a third of the park (Ranjeewa et al, 2018), probably due to the higher possibility of spotting animals in this area. A typical safari tour commencing at the main gate would usually cover the central part of the park between the Udawalawe and Mau Ara reservoirs.…”
Section: Practical Issues When Using Carrying Capacity Guidelines For Setting Limits To Visitor Loadsmentioning
confidence: 99%